2015
DOI: 10.1248/bpb.b15-00121
|View full text |Cite
|
Sign up to set email alerts
|

Determination and Pharmacokinetic Study of Pachymic Acid by LC-MS/MS

Abstract: Poria cocos is a well-known medicinal plant widely used in China and other East Asian countries owing to its various therapeutic effects. Pachymic acid (PA) is a bioactive lanostrane-type triterpenoid from Poria cocos. In this paper, a method of high-performance liquid chromatographic (LC) coupled with triple quadrupole tandem mass spectrometry (QQQ-MS/MS) was developed and validated to investigate the concentration of PA in rat plasma. Samples were prepared by a liquid-liquid extraction, and chromatographic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 19 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…In addition, a study performed by Wang et al reported main pharmacokinetic parameters of pachymic acid, a bioactive triterpenoid isolated from Poria cocos, after oral intake. The half-life was 4.96 ± 1.33 h and t max was 0.75 ± 0.14 h [92].…”
Section: Clinical Researchmentioning
confidence: 94%
“…In addition, a study performed by Wang et al reported main pharmacokinetic parameters of pachymic acid, a bioactive triterpenoid isolated from Poria cocos, after oral intake. The half-life was 4.96 ± 1.33 h and t max was 0.75 ± 0.14 h [92].…”
Section: Clinical Researchmentioning
confidence: 94%
“…After sublingual vein injection of PA at a dose of 30 mg/kg, the pharmacokinetic parameters in rat plasma were obtained using HPLC with half-life (t 1 / 2 ) at 8.79±6.80 h, clearance (CL) at 0.53±0.28 l/h, area under the curve (AUC) 0-∞ at 18.90±9.39 µ g h/ml and mean residence time 0-∞ at 12.58±9.95 h ( 89 ). Following oral administration of PA (10 mg/kg), the main pharmacokinetic parameters in rat plasma using liquid chromatography tandem mass spectrometry (MS) were elimination half-life at 4.96±1.33 h, AUC 0-∞ at 1466.9±361.7 ng h/ml and CL at 6.82±1.73 l/h ( 90 ). Determination of PA (12.3 mg/kg) in rats after oral administration using UPLC-Q-Orbi-trap MS demonstrated that the pharmacokinetic parameters were terminal half-life at 11.51±9.90 h, AUC 0-∞ at 336.29±161.99 ng h/ml and CL at 45.07±73.64 L/h.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Therefore, the beneficial effects of PC on estrogen-deprivation-induced bone loss may be due to the activity of the constituents mentioned above. In addition, numerous pharmacokinetic studies have reported that dehydrotumulosic acid, poricoic acid A, polyporenic acid C, dehydropachymic acid, pachymic acid, and dehydrotrametenolic acid are absorbed, distributed, metabolized, and excreted after oral administration of PC [9,26,30]. Further studies are needed to elucidate the precise mechanisms of components responsible for the anti-osteoporotic activity shown by PC and its effects on bone homeostasis.…”
Section: Phytochemical Constituents Of Pcmentioning
confidence: 99%